Analisis Dinamika Pasar Kerja di Era Pemulihan Ekonomi: Pengaruh Output Ekonomi, Upah, Pendidikan, dan Investasi Asing di Indonesia - Azzahro, Septin; Samudra, Ribka Widayati; Ashar, Khusnul; Setyanti, Axellina Muara (Fakultas Teknik Universitas Maritim AMNI Semarang, 2025)
This study aims to analyze the influence of Gross Regional Domestic Product (GRDP), Average Years of Schooling (AYS), Provincial Minimum Wage (PMW), and realized foreign investment on the Labor Force Participation Rate (LFPR). The background of this research is based on the urgency of understanding labor market dynamics as a strategic indicator of economic development, particularly following the COVID-19 pandemic. A quantitative approach is utilized in this study, applying panel data regression across 34 provinces in Indonesia during the period 2020–2023. The analysis results indicate that GRDP, AYS, PMW, and foreign investment have a positive and significant influence on LFPR. An increase in the average years of schooling reflects an improvement in human resource quality, which encourages labor force participation. The rise in the Provincial Minimum Wage plays a role in strengthening incentives to enter the formal labor market. GRDP growth demonstrates an economic expansion effect that broadens job opportunities, while foreign investment serves as a catalyst in the creation of new employment opportunities.These findings offer important implications for the formulation of strategic policies in the fields of employment, education, and investment, specifically in strengthening the involvement of the productive workforce in Indonesia's development and output creation.